Improving Tuberculosis Preventive Therapy Uptake: A Cluster-randomized Trial of Symptom-based Versus Tuberculin Skin Test–based Screening of Household Tuberculosis Contacts Less Than 5 Years of Age. (24th May 2019) - Salazar-Austin, Nicole; Cohn, Silvia; Barnes, Grace Link; Tladi, Molefi; Motlhaoleng, Katlego; Swanepoel, Catharina; Motala, Zarina; Variava, Ebrahim; Martinson, Neil; Chaisson, Richard E
Abstract: Background: Tuberculosis preventive therapy (TPT) is highly effective at preventing tuberculosis disease in household child contacts (<5 years), but is poorly implemented worldwide. In 2006, the World Health Organization recommended symptom-based screening as a replacement for tuberculin skin testing (TST) to simplify contact evaluation and improve implementation. We aimed to determine the effectiveness of this recommendation. Methods: We conducted a pragmatic, cluster-randomized trial to determine whether contact evaluation using symptom screening improved the proportion of identified child contacts who initiated TPT, compared to TST-based screening, in Matlosana, South Africa. We randomized 16 clinics to either symptom-based or TST-based contact evaluations. Outcome data were abstracted from customized child contact management files. Results: Contact tracing identified 550 and 467 child contacts in the symptom and TST arms, respectively (0.39 vs 0.32 per case, respectively; P = .27). There was no significant difference by arm in the adjusted proportion of identified child contacts who were screened (52% in symptom arm vs 60% in TST arm; P = .39). The adjusted proportion of identified child contacts who initiated TPT or tuberculosis treatment was 51.5% in the symptom clinics and 57.1% in the TST clinics (difference −5.6%, 95% confidence interval −23.7 to 12.6; P = .52). Based on the district's historic average of 0.7 child contacts per index case, 14% and 15% of child contacts completed 6 months of TPT in the symptom and TST arms, respectively ( P = .89). Conclusions: Symptom-based screening did not improve the proportion of identified child contacts evaluated or initiated on TPT, compared to TST-based screening. Further research is needed to identify bottlenecks and evaluate interventions to ensure all child contacts receive TPT. Clinical Trials Registration: NCT03074799. Abstract : This randomized controlled trial evaluated the effectiveness of the World Health Organization's 2006 recommendation for a symptom-based screening on the uptake of tuberculosis preventive therapy (TPT) among child tuberculosis contacts. Despite this simplified evaluation process, TPT uptake remains poor.